Pengaruh Publisitas dan Kualitas Pelayanan Terhadap Citra Merek (Survei Terhadap Pelanggan Colour Wedding) - Anggun Destania; Laela Nuur Husaini; Rinda Samarsya; Siti Nurul Janah; Chindy Nur Juniasih; Rifkah Fauziah (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
It cannot be denied that currently technology has an important role in helping business actors to brand the products or services they provide, one of which is through publicity activities. The role played by business actors through publicity activities is to protect, manage and maintain the most valuable assets for business actors, namely the image that will be able to increase trust and brand image. Apart from publicity activities, paying attention to the quality of service for business actors in the service sector can also help in forming the brand image of a business. This research aims to determine the influence of publicity and service quality on the formation of the Color Wedding brand image. The research results show that the calculated F value = 99.344 with a significance level of .000b. This proves that the significance value is smaller than 0.05, so it can be concluded that the publicity variable (X1), service quality variable (X2) have an influence on the brand image variable (Y). There is an influence between publicity activities and improving service quality on the formation of brand image.